FeOOH-Templated synthesis of hollow porous platinum nanotubes as superior electrocatalysts towards methanol electrooxidation - Sun, Hao; Qi, Lijuan; Jiang, Xian; Fu, Gengtao; Xu, Lin; Sun, Dongmei; Gu, Zhenggui; Tang, Yawen (New journal of chemistry, 2017)
Metallic nanomaterials with a hollow and porous structure have attracted a great deal of interest in electrocatalysis due to their high surface area, abundant active-sites and improved metal utilization efficiency. Herein, we report an effective layer-by-layer assembly strategy to prepare a novel type of hollow porous Pt nanotube (Pt-NT) using polyelectrolyte-modified FeOOH nanorods as templates. To our knowledge, the utilization of FeOOH nanorods as templates to synthesise hollow porous Pt nanostructures has not been reported. The obtained Pt-NTs present the combined merits of a one-dimensional (1D) hollow architecture, a reactant accessible porous-surface and a large surface area (37.8 m 2 g −1 ). As a result, superior catalytic activity and stability for the methanol oxidation reaction (MOR) are achieved with the Pt-NTs as an anode catalyst. Compared to a commercial Pt-black catalyst, the Pt-NTs exhibit a factor of 1.4 and 1.2 enhancement in mass activity (231 A g −1 ) and specific activity (11.8 A m −2 ) for the MOR, respectively.